Need an analysis of virtual reality-based learning media for French listening skills of DELF A1 - Andika, Yunilis; Ekowati, Sri Harini; Ismail, Subur; Hierro, Izza Almaida (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Interesting learning is the dream of every educator and student, especially in distance learning. The use of technology is the primary key in applying learning media to support 21st-century skills. The main reason for analyzing the need for virtual reality-based learning media is that there are not yet varied learning media and the difficulty of making and finding the appropriate learning media, especially for French listening skills. This study aimed to analyze the needs related to virtual reality-based learning media in the DELF A1 French listening skills course appropriate to the current situation during the pandemic. This study focuses on the perspectives of lecturers and students regarding the need for virtual reality-based learning media, especially in the French listening skills of DELF A1 at the French Language Education Study Program. This research used the research and development design. Data were collected through observation, documentation, and questionnaire distributed to 55 students and 6 lecturers. Data analysis was carried out using three phases, including data reduction, data display, and conclusion drawing/verification. This study showed that the use of virtual reality-based learning media in listening skills is crucial and needed by lecturers and students. It was proven with the lecturers and students’ statements that 70% of the lecturers strongly agreed and 30% agreed, and 67% of the students agreed and 33.3% strongly agreed. Therefore, this needs to be done so that it can be a solution for students and lecturers regarding the application of technology-based interactive learning media and the addition of teaching materials from the Alter Ego1+ book used in the French Language Education Study Program. As a result, the learning atmosphere is more interesting and effective and invites students to feel the sensation of being in a real situation in the conversation.